Spiritual and Moral Attitude of A Leader and The Requirements Imposed On It - Sulaymonova Dildora Kodirovna (Researchparks Publishing, 2024)
This article talks about the moral and ethical qualities of public servants who set an example by their actions, as well as the ethical rules and requirements that must be observed. In particular, general recommendations are given on the opinions and views of thinkers and scholars, highlighting the requirements for a public servant of the state. This is also regulated by laws, judgements and constitutional frameworks.